BODIPY-based organic color conversion layers for WLEDs. (February 2020) - Yuce, Hurriyet; Guner, Tugrul; Dartar, Suay; Kaya, Beraat U.; Emrullahoglu, Mustafa; Demir, Mustafa M.
Abstract: The usage of organic dyes in phosphor conversion layer of WLED is an attractive approach since they have high molar extinction coefficient and photostability. Various types of organic pigments have been employed for this purpose such as BODIPY, perylene diimide, Rhodamine B, pyrene, Nile red, etc. Among those, BODIPY-based organic dyes appear to be promising candidate for white light generation. In this work, for the first time, red and green emitting BODIPY-based organic molecules have been used as colour conversion layer. These molecules were associated with PMMA in DMF solution and the resulting solution was subjected to electrospinning. Colorful electrospun mats were embedded into PDMS matrix and their free-standing PDMS composite films were used as color conversion layers over blue LED to produce white light such that CRI of 95 and CCT of 4200 K was achieved. These values show that BODIPY-based organic molecules containing fiber composites are promising candidates to be used as color conversion layers for white light applications. Highlights: Red and green emitting BODIPY-based organic molecules have been employed. Colorful BODIPY-based electrospun mats are employed as color conversion layers. Free-standing composite films are obtained by embedding electrospun mats into PDMS. CRI of 95 and CCT of 4200 K was achieved by employing them over blue LED. BODIPY-based organic molecules are promising candidates for WLED applications.